DETERMINATION OF THE BIOACCUMULATION FACTORS OF ORGANOCHLORINE PESTICIDES (OCPs) AT SOME SPECIES OF BIVALVE MOLLUSKS IN SOAI RAP ESTUARY - HO CHI MINH CITY - Tong, Nguyen Xuan; Huong, Tran Thi Thu; Huong, Mai; Thuy, Duong Thi (Vietnam Journal of Marine Science and Technology, 2019)
Deposited sediments contain organochlorine pesticide chemicals which can pollute surface water as well as aquatic ecosystems. In this study, the accumulation of organochlorine pesticide chemicals in the bivalve mollusk group including Pacific oyster (Crassostrea gigas, Thunberg, 1793), green mussel (Perna viridis), blood scallop (Anadara granosa) ), white clam (Meretrix lyrata) and pearl oyster (Pinctada maxima) at Soai Rap estuary, Ho Chi Minh city was selected as subject of this research because of their high bioaccumulation capacity; their sedentary life, organic residue filter feeding habit and the ability to clean the lagoon environment. The pesticide chemicals were analyzed on GC-ECD system. Result of this research shows the different levels of accumulation in meat tissues of 5 species but they are lower than the allowable value of MARD 193:2004 - The bivalve mollusk harvest zone - Conditions to ensure food hygiene and safety. The results of calculating the Bio-Accumulation Factor (BAF) and Biota Sediment Accumulation Factor (BSAF) of the five species have shown that the bioaccumulation of organochlorine pesticides (OCPs) of bivalve mollusks in the area is natural tendency. BAF and BSAF of Crassostrea gigas were 56.672 and 0.429, Perna viridis were 66.730 and 0.608, Anadara granosa were 123.884 and 1.974, Meretrix lyrata were 52.060 and 0.489, Pinctada maxima were 115.176 and 1.076, respectively